Réponses

2013-07-03T15:37:42+02:00

a.   Comme :

 

                             2(0) - 5  ≤  3/2 - 11(0)       ⇔       -5 ≤ 3/2

 

      ce qui est vrai, 0 est solution de l'inéquation.

 

 

      Comme :

                2(1) - 5  ≤  3/2 - 11(1)       ⇔       2 - 5  ≤  3/2 - 22/2       ⇔       -6/2  ≤  -19/2

 

     ce qui est faux, 1 n'est pas solution de l'inéquation.

 

 


b.  On a :

                     

                  2x - 5  ≤  3/2 - 11x       ⇔       2x +11x  ≤  3/2 + 5       ⇔       13x  ≤  13/2

                                 

                                                    ⇔       x ≤ 1/2

 

 

 

c.   Cf. pièce jointe.